Edmund Monsiel – the forgotten genius from Wożuczyn.Observations about the exhibition at Gardzienice Gallery in Lublin - Welcz, Henryk (Current Problems of Psychiatry, 2011)
Edmund Monsiel was born on 12th November 1897 in Wożuczyn, a small settlement located between Tomaszów Lubelski and Łaszczów, as the sixth child of Mikołaj and Karolina of the Dutkowscy family. He died on 8th April 1962 in Tomaszów Lubelski. He came from a indigent family, his father was a carpenter, while roots of his family are associated with a French soldier of Napoleon’s army who stayed in Poland after the army had pulled out of Russia in 1812. The Second World War found Monsiel in Łaszczów, where also, after a takeover of his shop and house by Germans, an execution took place. The execution was in retaliation for a raid on the German gendarmerie station in 1942. Among seventy two people who were killed during the execution were his brother-in-law with daughter. Since then Edmund Monsiel had changed and started to hide, at first in Łaszczów, then he settled in the attic of his brother’s place in Wożuczyn - Cukrownia. He stopped taking care of himself; he isolated himself from other people and lost touch with them.After his death 566 drawings were fund, where some of them were padlocked in chest with three padlocks. The first dated drawings were created in Łaszczów during Passion Week in 1943. He almost always used hard pencil and the bases for his drawings were scraps of paper, book covers and office papers. The drawings show figures, possibly his relatives. There are no titles on them but reminders of moralizing and religious character, sometimes in the form of a prayer. The characteristic feature is filling the whole surface with faces or their parts.The composition, apparently open, is limited with edges of paper and its centre is constituted by a figure which establishes hierarchy in the whole exposition. The rich ornament in the background is made up of dozens of tiny heads with eyes gazing at different directions.310 H. WelczIn the exhibition at Gardzienice Gallery in Lublin, 16 drawings were shown, in which the lack of perspective is visible, apart from the work showing the interior of the church in Wożuczyn. That could prove that he knew the principles of usage of perspective and consciously rejected it in the majority of his works. It is puzzling that there is no precise knowledge of the artist and that he is absent in awareness of people living near to him and of those interested in the art, especially this labelled as outsider art (artbrut). The analysis of his works is an excellent lesson of psychopathology for the young psychiatrists and a very interesting subject for art historians. We should be grateful particularly to Gardzienice Gallery in Lublin placed in the Grodzka Street, because it, as one of few, organised and made the drawings of the forgotten genius from Wożuczynavailable to the wider audience.